Fabrication of bacterial nanocellulose/polyethyleneimine (PEI-BC) based cationic adsorbent for efficient removal of anionic dyes - Thorat, Meghana N.; Jagtap, Ashish; Dastager, Syed G. (Journal of Polymer Research, 2021)
A bacterial cellulose (BC) based adsorbent was prepared by using polyethyleneimine (PEI) using epichlorohydrin as a cross-linker. The physicochemical characterization of the of the developed adsorbent was carried out using FTIR, BET analysis and SEM, respectively. The dye removal efficiency of the adsorbent was assessed towards two anionic model dyes viz. congo red (CR) and reactive red 120(RR). The kinetic data for the removal of both the anionic dyes were fitted better using pseudo-second-order model. Langmuir model describes well the process of adsorption with predicted maximum adsorption capacity (q(max)) 515.46 and 300.3 mg L-1 for CR (at pH 6.0) and RR (at pH 3.0) respectively. The adsorption-desorption study showed that PEI-BC adsorbent is effective with more than 90% dye removal efficiency even after four cycles. Furthermore, the bactericidal activity of the adsorbent was analysed using Escherichia coli and Staphylococcus aureus and adsorbent showed good inhibition against both test organisms. The study reveals that PEI-BC adsorbent can be a good candidate for water remediation purpose bearing multifunctional behaviour.
Keywords: adsorbent; Anionic dyes; Bacterial cellulose; Bactericidal; Polyethyleneimine